2019
DOI: 10.3390/app9071433
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Assistant System of Clean Intermittent Catheterization for Neurogenic Bladder Dysfunction Patients

Abstract: Clean intermittent catheterization (CIC) is one of the methods currently used to prevent overdistention of the bladder in patients with neurogenic bladder dysfunction (NBD). It is also helpful in preventing urinary tract infection and retaining the function of the bladder. Voiding diary and social behavior are necessary for the patients to maintain their physical and mental health, nevertheless there are currently no good assistant systems to help them achieve these goals. In this study, we propose a CIC assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
1
0
2
Order By: Relevance
“…Socio-Demographic Characteristics of the Study Sample indicated that the majority of them (73%) were (18-32) years old , (27%) were (33-42) years old, (58%) were single (42%) were married.Forty two percent graduated from primary school, (27%) of those were middle school graduated (23%) were secondary graduate, (31%) were does not work, and (31%) were employee, (23%) were free business, and (50%) of those in median level of economic status.Huang C. et al, (2019) 13 they are established a study development of an assistant system of clean intermittent catheterization for neurogenic bladder dysfunction patients, and found the mean of age participants (39.25). Moreover, Afsar S et al (2013) 14 reported that most of participants (55.9%) of sample with primary graduate.…”
Section: Discussionmentioning
confidence: 99%
“…Socio-Demographic Characteristics of the Study Sample indicated that the majority of them (73%) were (18-32) years old , (27%) were (33-42) years old, (58%) were single (42%) were married.Forty two percent graduated from primary school, (27%) of those were middle school graduated (23%) were secondary graduate, (31%) were does not work, and (31%) were employee, (23%) were free business, and (50%) of those in median level of economic status.Huang C. et al, (2019) 13 they are established a study development of an assistant system of clean intermittent catheterization for neurogenic bladder dysfunction patients, and found the mean of age participants (39.25). Moreover, Afsar S et al (2013) 14 reported that most of participants (55.9%) of sample with primary graduate.…”
Section: Discussionmentioning
confidence: 99%
“…Hastaların kendi kendine uyguladığı ya da bir başkasının yardımı ile uygulanan temiz aralıklı kateterizasyonun özellikle, gece idrara çıkma sıklığını azaltarak uyku kalitesini artırdığı ve gündüz yorgunluğunu azalttığı, mesane yönetimi sağlayarak yaşam kalitesini iyileştirdiği görülmektedir (11,12). Temiz aralıklı kateterizasyon, bireye istediği zaman veya yerde mesanesini boşaltma ve öz bakımını sağlama fırsatı verdiğinden bireye bağımsızlığını koruma yeteneği sunmakla birlikte bireyin günlük ve sosyal aktivitelere katılmasına olanak sağlayarak yaşam kalitesini olumlu etkiler (11)(12)(13). Bununla birlikte kateterizasyonun gün içerisinde birkaç kez uygulanması hasta birey üzerinde olumsuz fiziksel ve psikolojik etkiye neden olabilir (11).…”
Section: Introductionunclassified
“…Temiz aralıklı kateterizasyon, bireye istediği zaman veya yerde mesanesini boşaltma ve öz bakımını sağlama fırsatı verdiğinden bireye bağımsızlığını koruma yeteneği sunmakla birlikte bireyin günlük ve sosyal aktivitelere katılmasına olanak sağlayarak yaşam kalitesini olumlu etkiler (11)(12)(13). Bununla birlikte kateterizasyonun gün içerisinde birkaç kez uygulanması hasta birey üzerinde olumsuz fiziksel ve psikolojik etkiye neden olabilir (11).…”
Section: Introductionunclassified